AMAZON - Jackson, Tom, 1972- (London : DK, 2022)
Visit one of the most incredible natural environments, to discover the Amazon's plants and wildlife, and its people. A unique, beautifully illustrated guide to the beauty and diversity of the Amazon - the rainforest and the river, its flora and fauna, and the people who live in the region. Read about the most biodiverse tract of tropical rainforest in the world and the vast river that winds its way through it. Eyewitness Amazon profiles everything from the birds, animals, and insects that live there to the nine South American countries it extends across. Using striking full-colour photographs and illustrations, discover why this ecosystem is so important to the whole world along with amazing facts, infographics, and statistics to see the Amazon as never before.
Previous edition: 2015.
Includes index.
Includes wall chart.
Keywords: Rain forests -- Amazon River Region -- Juvenile literature; Natural history -- Amazon River Region -- Juvenile literature; Amazon River -- Juvenile literature; Amazon River Region -- Juvenile literature